Low voltage varistors, circuit boards, semiconductor component packages and interposers
Patent Information
- Application Number
- JP2022504340
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-02
- Filing Date
- 2021-03-01
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-03-01
Smart Images

Figure 0007634285000005 
Figure 0007634285000006 
Figure 0007634285000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a varistor comprising a cured product of a resin composition for forming a low-voltage varistor. [Background technology]
[0002] Patent Documents 1 to 4 describe techniques relating to varistors.
[0003] Patent Document 1 describes a multilayer ceramic varistor in which ceramic layers mainly composed of SrTiO3 and internal electrodes are alternately laminated in a sintered body, and the ceramic layers are formed of a ceramic with a void volume occupancy rate of 1.35 to 4.85%. Patent Document 1 also describes that the capacitance C of the examples is 5.5 to 32.0 nF.
[0004] Patent Document 2 describes a voltage switchable dielectric (VSD) material composition. Patent Document 2 describes that the VSD material composition contains a binder and high aspect ratio (HAR) particles including conductive particles and / or semiconductor particles. Also, FIG. 3C of Patent Document 2 describes that the change in electrical resistance as a varistor occurs in the range of 500 to 100V.
[0005] Patent Document 3 describes a paste for forming a varistor element, which contains a resin composition comprising (A) an epoxy resin, (B) a curing agent, and (C) carbon nanotubes, in which the carbon nanotubes contain 70% by weight or more of semiconducting single-walled carbon nanotubes.
[0006] Patent Document 4 describes a varistor-forming resin composition that contains (A) an epoxy resin, (B) a curing agent, (C) carbon nanotubes, and (D) a dispersant. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2001-93706 A [Patent Document 2] U.S. Patent No. 7,695,644 [Patent Document 3] U.S. Patent No. 10141090 [Patent Document 4] International Publication No. 2019 / 116955 Summary of the Invention
[0008] A varistor is an element (electronic or electrical component) that has a property that when the voltage between a pair of electrodes is low, the electrical resistance is high, and when the voltage between the pair of electrodes exceeds a certain level, the electrical resistance drops suddenly. In general, a varistor has a structure in which a material having a nonlinear resistance characteristic is disposed between a pair of electrodes. Examples of materials having a nonlinear resistance characteristic include silicon carbide, zinc oxide, and strontium titanate.
[0009] In order to improve the performance and reduce the cost of varistors, it is necessary to discover and develop new materials for varistors.
[0010] In semiconductor devices and the like, there are applications requiring low-voltage varistors that can operate at low voltages (for example, 10 V or less, preferably 8 V or less, and more preferably 7 V or less).
[0011] Also, varistors are required to have excellent overvoltage protection characteristics: that is, a varistor with excellent performance is required to have a rapid drop in electrical resistance with an increase in applied voltage (a high nonlinearity coefficient α, described later).
[0012] Moreover, varistors used in high frequency regions are required to have low capacitance.
[0013] An object of the present invention is to provide a varistor that is capable of operating at a low voltage and has excellent performance.
[0014] In order to solve the above problems, the present invention has the following configuration.
[0015] (Configuration 1) A first aspect of the present invention is a low-voltage varistor comprising a cured product of a resin composition for forming a low-voltage varistor, The resin composition for forming a low-voltage varistor comprises (A) at least one selected from carbon nanotubes and carbon aerogels; (B) at least one selected from an epoxy resin and an acrylic resin; A low voltage varistor comprising:
[0016] (Configuration 2) A second aspect of the present invention is the low-voltage varistor of the first aspect, characterized in that the varistor voltage is 0.3 to 10 V when the inflow current of the low-voltage varistor is 0.1 mA.
[0017] (Configuration 3) The third aspect of the present invention is to provide a current-voltage characteristic of a low-voltage varistor as follows: I=KV α (where V is the applied voltage, I is the inflow current, K is a constant, and α is a nonlinearity coefficient), the low-voltage varistor has a nonlinearity coefficient α of 7 to 20.
[0018] (Configuration 4) A fourth aspect of the present invention is a low-voltage varistor according to any one of the first to third aspects, characterized in that the capacitance is 0.5 to 200 pF.
[0019] (Configuration 5) A fifth aspect of the present invention is a circuit board having a low-voltage varistor according to any one of the first to fourth aspects mounted thereon.
[0020] (Configuration 6) A sixth aspect of the present invention is a semiconductor component package incorporating a low-voltage varistor according to any one of the first to fourth aspects.
[0021] (Configuration 7) A seventh aspect of the present invention is an interposer equipped with a low-voltage varistor according to any one of the first to fourth aspects.
[0022] According to the present invention, it is possible to provide a varistor that is capable of operating at a low voltage and has excellent performance. [Brief description of the drawings]
[0023] [Figure 1] FIG. 2 is a schematic plan view of an electrode used in a varistor according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic plan view of a varistor according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a diagram showing the current-voltage characteristics of the varistor of Example 1. [Figure 4] FIG. 13 is a diagram showing the current-voltage characteristics of the varistor of Example 2. [Diagram 5] FIG. 4 is a diagram showing the current-voltage characteristics of the varistor of Comparative Example 1. [Figure 6] FIG. 13 is a diagram showing the current-voltage characteristics of the varistor of Comparative Example 2. [Figure 7] 1 is a SEM photograph (magnification: 10,000 times) of the porous carbon of Reference Example 1 of the present invention. [Figure 8] 1 is a SEM photograph (magnification: 100,000 times) of the porous carbon of Reference Example 1 of the present invention. [Figure 9] 1 is a SEM photograph (magnification: 10,000 times) of the porous carbon of Reference Example 2. [Figure 10] 1 is a SEM photograph (magnification: 100,000 times) of the porous carbon of Reference Example 2. [Figure 11] 1 is a SEM photograph (magnification: 10,000 times) of the porous carbon of Reference Comparative Example 2. [Figure 12] 1 is a SEM photograph (magnification: 100,000 times) of the porous carbon of Reference Comparative Example 2. [Figure 13] 1 is a Raman spectrum of the porous carbon of Reference Example 1. [Figure 14] 1 is a Raman spectrum of the porous carbon of Reference Example 2. [Figure 15] 1 is a Raman spectrum of the porous carbon of Reference Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings. Note that the following embodiments are forms for embodying the present invention, and are not intended to limit the scope of the present invention.
[0025] <Low voltage varistor> First, the low-voltage varistor of the present invention will be described. The low-voltage varistor of this embodiment includes a cured product of a resin composition for forming a low-voltage varistor. The resin composition for forming a low-voltage varistor will be described later.
[0026] A schematic diagram of an example of a varistor is shown in Fig. 2. The varistor shown in Fig. 2 has a structure in which a cured body 16 of a material having varistor properties (a resin composition for forming a low-voltage varistor) is placed on a pair of electrodes 14a and 14b as shown in Fig. 1. The structure of the varistor shown in Fig. 2 is merely an example, and any structure can be adopted as long as a material having varistor properties is placed between a pair of electrodes. For example, a structure in which a material having varistor properties is placed between electrodes placed parallel to a plane, a structure in which a pair of electrodes are placed three-dimensionally in a comb shape, etc. can be adopted.
[0027] A varistor is an electronic element (or electric element) that has nonlinear resistance characteristics. The relationship (current-voltage characteristic) between the voltage V (applied voltage) applied between the pair of electrodes 14a and 14b of the varistor and the current I (inflow current) that flows between both terminals at that time is I=K·V, where K is a constant. α The α in this approximation formula is called the nonlinearity coefficient. For normal ohmic resistors, α=1, but for varistors, α>1. If the nonlinearity coefficient α of a varistor is 7 or more, specifically, if α is between 7 and 20, it can be said to have excellent overvoltage protection characteristics.
[0028] By using the resin composition for forming a low-voltage varistor of this embodiment, it is possible to manufacture a varistor having excellent overvoltage protection characteristics, that is, a varistor having a nonlinearity coefficient α of 7 or more, specifically, α of 7 to 20.
[0029] The low-voltage varistor of this embodiment has a varistor voltage of preferably 0.3 to 10 V, more preferably 0.3 to 8 V, and even more preferably 0.3 to 7 V, when the inflow current of the low-voltage varistor is 0.1 mA. The low-voltage varistor of this embodiment is particularly suitable for use in applications where the varistor voltage is about 6 V when the inflow current of the low-voltage varistor is 0.1 mA. The low-voltage varistor of this embodiment can operate at a relatively low voltage compared to conventional varistors. Therefore, it can be said that the varistor of this embodiment has excellent characteristics as a low-voltage varistor.
[0030] The low-voltage varistor of this embodiment preferably has a capacitance of 0.5 to 200 pF, more preferably 0.5 to 180 pF, and even more preferably 0.5 to 160 pF. In this case, the capacitance can be measured using an oscillator frequency of 1 kHz. Compared with conventional varistors, the low-voltage varistor of this embodiment has a relatively low capacitance, and therefore low impedance at high frequencies. Therefore, it can be said that the varistor of this embodiment has excellent characteristics as a low-voltage varistor in the high-frequency region.
[0031] This embodiment is a circuit board equipped with the above-mentioned low-voltage varistor. The varistor of this embodiment can be preferably used as a low-voltage varistor in the high frequency range. Therefore, by mounting the varistor of this embodiment on a specified circuit board, a desired electronic circuit can be obtained.
[0032] This embodiment is a semiconductor component package equipped with the above-mentioned low-voltage varistor. The varistor of this embodiment can be preferably used as a low-voltage varistor in the high frequency range. Therefore, by mounting the varistor of this embodiment in a specified semiconductor component package, a semiconductor component package that enables a desired operation can be obtained.
[0033] This embodiment is an interposer equipped with the above-mentioned low-voltage varistor. The interposer is a substrate having a through electrode for achieving electrical continuity between the front and back surfaces of the substrate for high circuit integration. The varistor of this embodiment can be preferably used as a low-voltage varistor in the high frequency range. Therefore, by mounting the varistor of this embodiment on a specific interposer, a highly integrated electronic circuit that enables the desired operation can be obtained.
[0034] <Resin composition for forming low-voltage varistor> Next, the resin composition for forming a low-voltage varistor for forming a cured product of the low-voltage varistor of this embodiment will be specifically described. In this specification, the resin composition for forming a low-voltage varistor may be simply referred to as a "resin composition" (or "resin composition of this embodiment").
[0035] <Component (A)> The resin composition for forming a low-voltage varistor of this embodiment contains, as component (A), at least one selected from (A1) carbon nanotubes and (A2) carbon aerogel.
[0036] The carbon nanotubes (A1) contained in the resin composition for forming a low-voltage varistor will now be described.
[0037] Carbon nanotubes are substances in which a six-membered ring network made of carbon is arranged in a coaxial tube shape. Single-walled and multi-walled carbon nanotubes are known. Carbon nanotubes can be classified into metallic carbon nanotubes and semiconducting carbon nanotubes based on their electrical properties. The (A1) carbon nanotubes contained in the resin composition for forming a low-voltage varistor of this embodiment are single-walled carbon nanotubes.
[0038] The (A1) carbon nanotube is preferably a single-walled carbon nanotube. Specifically, the (A1) carbon nanotube may be a single-walled carbon nanotube (TUBALL SWCNT 93%) manufactured by OCSIAL. TUBALL SWCNT 93% is a single-walled carbon nanotube with an outer diameter of 1.6 nm±0.4 nm, a length of 5 μm or more, and a carbon nanotube content of 93% or more.
[0039] The content of the (A1) carbon nanotubes in the resin composition for forming a low-voltage varistor is preferably 0.01 to 2 parts by weight, more preferably 0.015 to 1 part by weight, even more preferably 0.02 to 0.1 part by weight, and particularly preferably 0.03 part by weight or more and less than 0.05 part by weight, relative to 100 parts by weight of the (B) epoxy resin.
[0040] The carbon aerogel (A2) contained in the resin composition for forming a low-voltage varistor will now be described.
[0041] Carbon aerogel is a porous carbon composed of nano-sized molecules covalently bonded and has high porosity. Hereinafter, carbon aerogel will also be referred to as porous carbon.
[0042] In this specification, carbon aerogel (porous carbon) is preferably porous carbon obtained by replacing a solvent contained in a gel-like mixture made from a carbon-containing material with a gas by supercritical drying and removing components other than carbon by pyrolysis.
[0043] Carbon aerogel (porous carbon) has many pores due to its manufacturing method. The size of the pores is less than 1 μm, and is a pore (nanopore) with a size on the order of nanometers. In general, the size of nanopores in porous carbon is 200 to 300 nm. The size of the pores can be obtained as the average of the diameters of multiple pores in a SEM photograph obtained by photographing the cross section of the porous carbon with a scanning electron microscope (SEM). The diameters of all the pores in the SEM photograph can be measured and the average can be obtained. In addition, the size of the pores can be obtained by measuring the diameters of, for example, 10 to 20 pores and averaging them.
[0044] Such porous carbon can be preferably used as a material for producing a varistor. Specifically, carbon aerogel powder (model number: PC16-151-10) manufactured by eM-TECH can be used as the (A2) carbon aerogel.
[0045] Carbon aerogel powder PC16-151-10 can be manufactured by Manufacturing Method 1 described later. Specific manufacturing conditions for carbon aerogel powder PC16-151-10 are shown below. Furfural and phloroglucinol (molar ratio of furfural:phloroglucinol 3:1) were dissolved in ethanol. The amount of ethanol used in this dissolution was adjusted so that the concentration of the total amount of furfural and phloroglucinol in the ethanol solution was 4% by weight. This ethanol solution of furfural and phloroglucinol was stirred and then left at room temperature to obtain a gelled solid. This gelled solid was replaced with air as a solvent by supercritical carbon dioxide liquid to produce an aerogel precursor. This aerogel was baked at 1000°C under a nitrogen stream to produce carbon aerogel PC16-151-10.
[0046] The content of the (A2) carbon aerogel in the resin composition for forming a low-voltage varistor is preferably 0.1 to 10 parts by weight, more preferably 0.5 to 5 parts by weight, even more preferably 1 to 4.5 parts by weight, and particularly preferably 2 to 4 parts by weight, relative to 100 parts by weight of the (B) epoxy resin.
[0047] Next, the porous carbon (carbon aerogel) that can be used in this embodiment will be specifically described.
[0048] The porous carbon that can be used in the present embodiment has a Raman spectrum measured by Raman spectroscopy, which has a peak at 1590 cm -1 The integrated intensity of the G band peak near 1350 cm was taken as IG. -1 When the integrated intensity of the D band peak near the IG peak is taken as ID, the ID / IG ratio is 2.0 or more. By using such porous carbon, it is possible to obtain a resin composition and a varistor-forming paste for producing a varistor having suitable varistor characteristics.
[0049] The porous carbon that can be used in this embodiment has a Raman scattering (Raman shift) wavenumber (wavenumber, usually in cm -1 ) has a certain Raman spectrum when the intensity of Raman scattering is measured. Generally, carbon-based materials have a certain Raman spectrum depending on the carbon bonding state. -1 Near and 1350cm -1 It has a peak around 1590cm -1 The peak near the center is the sp 2 This is thought to be a G-band peak due to hybrid orbitals. 1350cm -1 The peak near the center is the sp 3 This is considered to be a peak of the D band derived from hybrid orbitals. Since the D band is considered to be due to diamond-like amorphous carbon, the high intensity of the D band is considered to be due to the occurrence of disorder in the bond state of graphite. The porous carbon that can be used in this embodiment has a peak of 1590 cm-1 The integrated intensity of the G-band peak near I G And 1350cm -1 The integrated intensity of the D band peak near I D When I D / I G The characteristic of the present invention is that I is 2.0 or more. D / I G is preferably 2.1 or more and 3.0 or less, and more preferably 2.2 or more and 2.5 or less.
[0050] The integrated intensity of the G band peak is the area of the peak after subtracting the background noise from the G band peak in a Raman spectrum in which the intensity of Raman scattering is plotted against the wave number of Raman scattering. The same applies to the integrated intensity of the D band peak. Since the G band peak and the D band peak are close to each other, the G band peak and the D band peak can be separated by peak fitting using an appropriate function such as a Lorentzian function. Such a method of peak separation is known.
[0051] The porous carbon that can be used in this embodiment has a maximum intensity of the G band peak of M G The maximum intensity of the D band peak is M D Then, M D / M G It is preferable that the ratio is 0.80 or more.
[0052] The porous carbon that can be used in the present embodiment has a maximum intensity of the G band peak of M in a Raman spectrum obtained by plotting the Raman scattering intensity against the wave number of the Raman scattering. G The maximum intensity of the D band peak is M D Then, M D / M G It is preferable that the maximum intensity M of the G band peak is 0.80 or more. Gis the maximum value of the Raman scattering peak intensity in the G band after subtracting the background noise from the measured value in the wavenumber range that constitutes the G band peak. The maximum intensity M of the D band peak D The same is true for the maximum intensity M. Since the G-band peak and the D-band peak are close to each other, the G-band peak and the D-band peak can be separated by peak fitting using an appropriate function such as a Lorentzian function. G It is possible to calculate M D / M G is more preferably 0.80 or more and 3.0 or less, and further preferably 0.90 or more and 1.5 or less. By using such porous carbon, it is possible to more reliably obtain a resin composition and a varistor-forming paste for producing a varistor having suitable varistor characteristics.
[0053] Next, a method for producing the porous carbon (carbon aerogel) according to an embodiment of the present invention will be described.
[0054] [Manufacturing method 1] In a porous carbon production method 1 that can be used in this embodiment, the porous carbon can be produced by pyrolysis of a mixture of raw materials containing furfural and phloroglucinol.
[0055] (The process of preparing materials) The manufacturing method 1 of the porous carbon usable in this embodiment includes a step of preparing a material. In the step of preparing a material, first, a predetermined amount of furfural and phloroglucinol are prepared. In the porous carbon usable in this embodiment, the raw material preferably contains 100 to 500 parts by weight of furfural per 100 parts by weight of phloroglucinol, more preferably 120 to 340 parts by weight, and further preferably 160 to 310 parts by weight.
[0056] (Pretreatment process) The manufacturing method 1 includes a pretreatment step of dissolving phloroglucinol and furfural in ethanol to obtain an ethanol solution. In the pretreatment step, first, phloroglucinol is dissolved in ethanol. Next, furfural is dissolved in the ethanol solution of phloroglucinol. The amount of ethanol used in this dissolution can be such that the concentration of the total amount of phloroglucinol and furfural in the ethanol solution is 1 to 45% by weight, preferably 1.5 to 30% by weight, and more preferably 2 to 25% by weight. In the manufacturing method 1, the concentration of the total amount of phloroglucinol and furfural in the ethanol solution in the pretreatment step (raw material concentration in the solvent) is referred to as the initial concentration (% by weight).
[0057] (Gelling process) The manufacturing method 1 includes a gelation step for gelling the ethanol solution of phloroglucinol and furfural. In the gelation step, the ethanol solution of phloroglucinol and furfural obtained as described above is stirred and then allowed to stand at room temperature to obtain a gelled solid.
[0058] (Cleaning process) The manufacturing method 1 includes a washing step for washing the gelled solid. In the washing step, the gelled solid is washed. Ethanol can be used for washing, but is not limited thereto. Other alcohols can also be used. For example, washing can be performed by repeatedly adding ethanol to the gelled solid and discharging the added ethanol, thereby washing the gelled solid. The washing step can be performed until the color of the discharged ethanol disappears.
[0059] (Supercritical drying process) Manufacturing method 1 includes a supercritical drying step for the washed solid. The gelled solid after washing is taken out and subjected to supercritical drying. Specifically, the gelled solid is placed in a sealed container, and supercritical liquid CO2 is introduced into the sealed container under a predetermined pressure. After that, the state is maintained, and then the supercritical liquid CO2 is discharged. This step can be repeated as necessary.
[0060] (pyrolysis process) Manufacturing method 1 includes a thermal decomposition step for the solid after supercritical drying. In the thermal decomposition step, the solid after supercritical drying obtained as described above is placed in a furnace and heated to 800°C or higher (for example, 800°C to 1500°C, preferably 800°C to 1200°C, more preferably 800°C to 1000°C) at a heating rate of 0.8 to 1.2°C / min in a nitrogen atmosphere. After completion of the heating, the solid is maintained at that temperature for 5 to 60 minutes (preferably 20 to 30 minutes) for thermal decomposition. As a result, components other than carbon are removed, and porous carbon can be obtained.
[0061] (Crushing process) The manufacturing method 1 includes a pulverization step for pulverizing the porous carbon obtained by the pyrolysis step to obtain particles. In the pulverization step, the heated porous carbon is returned to room temperature and pulverized to obtain powdered porous carbon. In the pulverization step, the porous carbon can be pulverized so that the porous carbon has a predetermined particle size. In the pulverization step, the average particle size of the porous carbon is preferably 0.01 to 50 μm, more preferably 0.02 to 10 μm, from the viewpoint of workability and the like. The average particle size can be the particle size of 50% of the total particle cumulative value (average particle size: D50). The average particle size D50 can be obtained by performing particle size distribution measurement using a laser diffraction / scattering particle size distribution measuring device LA-960 (laser diffraction scattering method) manufactured by Horiba, Ltd., and obtaining the D50 value from the results of the particle size distribution measurement.
[0062] As described above, the porous carbon can be produced by the production method 1.
[0063] [Manufacturing method 2] In a porous carbon production method 2 that can be used in this embodiment, the porous carbon is produced by pyrolysis of a raw material containing polyimide.
[0064] (The process of preparing materials) The porous carbon manufacturing method 2 that can be used in this embodiment includes a step of preparing a material, in which predetermined amounts of pyromellitic anhydride and paraphenyldiamine are prepared.
[0065] (Pretreatment process) The manufacturing method 2 includes a pretreatment step for synthesizing a polyimide solution. In the pretreatment step of the manufacturing method 2, first, a polyamic acid solution can be synthesized using pyromellitic anhydride and paraphenyldiamine as materials. Dimethylacetamide and toluene can be used as the solvent in this synthesis. The total weight of the solvent (dimethylacetamide and toluene) relative to the total weight of pyromellitic anhydride and paraphenyldiamine can be selected so that the initial concentration of the synthesized polyamic acid solution is within a predetermined range. In the manufacturing method 2, the initial concentration (wt%) refers to the concentration of polyamic acid in the polyamic acid solution in the pretreatment step (the ratio of the total weight of pyromellitic anhydride and paraphenyldiamine, which are raw materials, to the weight of the polyamic acid solution after synthesis). The initial concentration is 1 to 45 wt%, preferably 1.5 to 30 wt%, more preferably 2 to 25 wt%, and even more preferably 10 to 15 wt%. The synthesis of the polyamic acid solution can be carried out by mixing pyromellitic anhydride and paraphenyldiamine and heating them. As a result, the polyamic acid solution can be synthesized. Next, a polyimide solution can be synthesized by adding predetermined amounts of pyridine and acetic anhydride to the polyamic acid solution obtained as described above.
[0066] (Gelling process) The manufacturing method 2 includes a gelation step for gelling the polyimide solution. In the gelation step, the polyimide solution obtained as described above is stirred. Thereafter, the solution is allowed to stand at room temperature to obtain a gelled solid.
[0067] (Washing process, supercritical drying process, heating process, and grinding process) The production method 2 includes a washing step, a supercritical drying step, a heating step, and a pulverization step. In the production method 2, after the above-mentioned gelation step, the washing step, the supercritical drying step, the heating step, and the pulverization step are performed in the same manner as in the production method 1, thereby making it possible to produce porous carbon.
[0068] The porous carbon that can be used in this embodiment has a peak temperature of pyrolysis of 800° C. or higher, preferably 800° C. to 1500° C., more preferably 800° C. to 1200° C., and even more preferably 800° C. to 1000° C., during the pyrolysis steps of Production Methods 1 and 2 when producing the porous carbon. By having the peak temperature of pyrolysis be a predetermined temperature, it is possible to more reliably obtain the porous carbon contained in a resin composition or the like for producing a varistor having suitable varistor characteristics.
[0069] The outline of the porous carbon described above is as follows.
[0070] (Structure of porous carbon 1) The porous carbon configuration 1 is a porous carbon, In the Raman spectrum of the porous carbon measured by Raman spectroscopy, -1 The integrated intensity of the G band peak near 1350 cm was taken as IG. -1 When the integrated intensity of the D band peak in the vicinity is ID, ID / IG is 2.0 or more. The porous carbon has pores with dimensions of less than 1 μm; The porous carbon is porous carbon for a varistor element.
[0071] By using the porous carbon of configuration 1, it is possible to obtain a resin composition and a paste for forming a varistor element for producing a varistor element having suitable varistor characteristics.
[0072] (Porous carbon structure 2) The porous carbon of configuration 2 is the porous carbon of configuration 1, in which MD / MG is 0.80 or more, where MG is the maximum peak intensity of the G band and MD is the maximum peak intensity of the D band.
[0073] By using the porous carbon of configuration 2, it is possible to more reliably obtain a resin composition and a paste for forming a varistor element for producing a varistor element having suitable varistor characteristics.
[0074] (Porous carbon structure 3) The porous carbon of configuration 3 is the porous carbon of configuration 1 or 2, in which the peak temperature of pyrolysis during production of the porous carbon is 800°C or higher and 1500°C or lower.
[0075] By using the porous carbon of configuration 3, it is possible to more reliably obtain the porous carbon contained in the resin composition or the like for producing a varistor element having suitable varistor characteristics.
[0076] (Porous carbon structure 4) Porous carbon configuration 4 is any of the porous carbons of configurations 1 to 3 produced by pyrolysis of a mixture of raw materials including furfural and phloroglucinol.
[0077] By using the porous carbon of configuration 4, it is possible to more reliably obtain the porous carbon contained in the resin composition or the like for producing a varistor element having suitable varistor characteristics.
[0078] (Structure of porous carbon 5) Porous carbon of constitution 5 is the porous carbon of constitution 4, in which the raw material contains 100 to 500 parts by weight of furfural per 100 parts by weight of phloroglucinol.
[0079] In the porous carbon of configuration 5, by adjusting the blending amount of furfural relative to phloroglucinol to an appropriate range, it is possible to more easily obtain porous carbon to be contained in a resin composition or the like for producing a varistor element having appropriate varistor characteristics.
[0080] (Porous carbon structure 6) The porous carbon of configuration 6 is any of the porous carbons of configurations 1 to 3, which is produced by pyrolysis of a raw material containing a polyimide.
[0081] In the porous carbon of configuration 6, by using polyimide as a raw material, it is possible to more reliably obtain the porous carbon contained in a resin composition or the like for producing a varistor element having suitable varistor characteristics.
[0082] By using the above-mentioned porous carbon (carbon aerogel), it is possible to obtain a resin composition for forming a low-voltage varistor for producing a low-voltage varistor having excellent performance.
[0083] <(B) component> The resin composition for forming a low-voltage varistor of this embodiment contains, as component (B), at least one selected from an epoxy resin and an acrylic resin.
[0084] The epoxy resin of component (B) preferably contains at least one selected from bisphenol A type epoxy resins, brominated bisphenol A type epoxy resins, bisphenol F type epoxy resins, biphenyl type epoxy resins, novolac type epoxy resins, alicyclic epoxy resins, naphthalene type epoxy resins, ether type epoxy resins, polyether type epoxy resins, and silicone epoxy copolymer resins.
[0085] By including a specific epoxy resin in the resin composition, a varistor can be manufactured in which the varistor material is appropriately cured.
[0086] The resin composition for forming a low-voltage varistor of this embodiment can use an acrylic resin as the component (B) instead of the above-mentioned epoxy resin or together with the epoxy resin. Specific examples of monomers for the acrylic resin include acrylic acid esters such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethylaminoethyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, and glycidyl acrylate. Examples of methacrylic acid esters include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, dimethylaminoethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and glycidyl methacrylate. In addition, a polymerization initiator can be used to polymerize the monomer to form the acrylic resin.
[0087] <(C) Hardener> The resin composition of this embodiment preferably contains an amine compound, a phenol, an acid anhydride, an imidazole compound, or a mixture thereof as the (C) curing agent. It is more preferable that the (C) curing agent contains an amine compound and an imidazole compound. By containing a specific curing agent in the resin composition, the epoxy resin can be appropriately cured when manufacturing the varistor. In the following description, the (B) component and the (C) curing agent may be referred to as the "resin component".
[0088] The curing agent contained in the resin composition of this embodiment preferably contains an imidazole compound. As the imidazole compound, imidazole and imidazole derivatives can be used. In the varistor of this embodiment, when the curing agent contains an imidazole compound, particularly imidazole, a varistor having better varistor characteristics, specifically a high nonlinearity coefficient α can be obtained. Specifically, as an imidazole-based curing agent, "2P4MHZ-PW" manufactured by Shikoku Kasei Corporation can be used. In addition, when the curing agent contains both an imidazole compound (particularly imidazole) and an amine compound other than the imidazole compound, a varistor having an even higher nonlinearity coefficient α can be obtained.
[0089] The amine compound other than the imidazole compound can be selected from aliphatic amines, alicyclic amines, aromatic amines, 3,3'-diethyl-4,4'-diaminodiphenylmethane, and diethyltoluenediamine. In particular, the amine compound can be preferably 3,3'-diethyl-4,4'-diaminodiphenylmethane (commercially available as an aromatic amine-based hardener "KAYAHARD AA" (manufactured by Nippon Kayaku Co., Ltd.)) and / or diethyltoluenediamine (commercially available as "Ethacure" manufactured by Albemarle Corporation).
[0090] When the curing agent contained in the resin composition of this embodiment contains an imidazole compound, the weight ratio of the imidazole compound contained in the total of the resin components (component (B) and curing agent (C)) is preferably 1 to 20% by weight, more preferably 2 to 15% by weight, and even more preferably 5 to 10% by weight. By blending the imidazole compound in a predetermined amount, it is possible to reliably obtain a varistor having a high nonlinearity coefficient α.
[0091] When the curing agent contained in the resin composition of this embodiment contains an amine compound other than an imidazole compound, the weight ratio of the amine compound contained in the total of the resin components (component (B) and curing agent (C)) is preferably 10 to 35% by weight, more preferably 15 to 30% by weight, and even more preferably 20 to 27% by weight. By using a predetermined amount of the amine compound other than the imidazole compound, it is possible to reliably obtain a varistor having a high nonlinearity coefficient α.
[0092] The resin composition of this embodiment and the varistor-forming paste described below preferably do not contain any inorganic components (fillers, etc.) other than the porous carbon, i.e., are filler-less. When the resin composition of this embodiment is used, even if a resin composition and varistor-forming paste having a simple structure that does not contain inorganic components such as fillers are used, a varistor having suitable varistor characteristics can be manufactured.
[0093] <Varistor forming paste> A paste for forming a varistor can be obtained by using the resin composition for forming a low-voltage varistor of the present embodiment described above. The resin composition for forming a low-voltage varistor of the present embodiment can be used as a paste for forming a varistor as it is. However, in order to ensure good application of the paste during screen printing or the like, the paste for forming a varistor can further contain (D) a dispersant and a solvent.
[0094] The varistor-forming paste of this embodiment may further contain a dispersant (D). The dispersant (D) preferably contains at least one selected from the group consisting of anionic surfactants, cationic surfactants, amphoteric surfactants, nonionic surfactants, hydrocarbon surfactants, fluorine surfactants, silicon surfactants, polycarboxylic acids, polyether carboxylic acids, polycarboxylates, alkyl sulfonates, alkylbenzene sulfonates, alkyl ether sulfonates, aromatic polymers, organic conductive polymers, polyalkyl oxide surfactants, inorganic salts, organic acid salts, and aliphatic alcohols. The dispersant (D) is preferably blended in an amount of 0.05 to 1 part by weight, more preferably 0.1 to 0.7 parts by weight, per 100 parts by weight of the total of the above-mentioned resin composition (epoxy resin, curing agent, and porous carbon).
[0095] The varistor-forming paste of this embodiment may contain a solvent. Examples of the solvent include aromatic hydrocarbons such as toluene and xylene, ketones such as methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone, esters such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether and corresponding acetates, and terpineol. The solvent is preferably blended in an amount of 2 to 10 parts by weight per 100 parts by weight of the resin composition (epoxy resin, curing agent and porous carbon) described above.
[0096] The varistor-forming paste of this embodiment may further contain at least one selected from the group consisting of colorants such as inorganic pigments and organic pigments, ion trapping agents, flame retardants, silane coupling agents, leveling agents, thixotropic agents, elastomers, curing accelerators, metal complexes, dispersants, and antifoaming agents.
[0097] The varistor-forming paste of this embodiment can be produced by mixing at least one of the above-mentioned (A) carbon nanotubes and carbon aerogel, at least one of (B) epoxy resin and acrylic resin, and optionally other components such as (C) hardener and solvent in a mixer such as a meteor mixer, dissolver, bead mill, Raikai machine, triple roll mill, rotary mixer, or twin-shaft mixer. In this way, a resin composition suitable for producing a varistor can be produced. The varistor-forming paste of this embodiment can be prepared into a varistor-forming paste having a viscosity suitable for screen printing, immersion, or other desired coating or wiring forming methods.
[0098] The varistor-forming paste of the present embodiment described above can be applied so as to come into contact with a given electrode, and then cured, thereby producing a varistor with suitable varistor characteristics. Examples of application methods include screen printing and dipping.
[0099] According to this embodiment of the present invention, a varistor capable of operating at a low voltage and having excellent varistor characteristics can be obtained. EXAMPLES
[0100] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the present invention is not limited to these.
[0101] <Materials and blending ratios of resin compositions in the examples> The materials used in the manufacture of the resin compositions for forming low-voltage varistors in the examples are as follows. The weight proportions of the materials in the examples and comparative examples are shown in Table 1. The weight proportions of each component shown in Table 1 are all shown in parts by weight, with the weight of (B) epoxy resin being 100 parts by weight.
[0102] As the component (A), the following (A1) carbon nanotubes and (A2) carbon aerogel were used.
[0103] As the (A1) carbon nanotube, a single-walled carbon nanotube (TUBALL SWCNT 93% manufactured by OCSIAL) was used. The (A1) carbon nanotube was used in Example 1.
[0104] As the (A2) carbon aerogel, carbon aerogel powder (eM-TECH PC16-151-10) was used. The carbon aerogel powder (eM-TECH PC16-151-10) was produced by the above-mentioned production method 1. At that time, the molar ratio of furfural:phloroglucinol was set to 3:1, and the amount of ethanol during dissolution was adjusted so that the concentration of the total amount of furfural and phloroglucinol in the ethanol solution was 4% by weight. In addition, the precursor aerogel was baked at 1000°C under a nitrogen stream to produce carbon aerogel powder (PC16-151-10). The (A2) carbon aerogel was used in Example 2.
[0105] (B) Epoxy resin The epoxy resin used in Example 1 is the following epoxy resin B1, and the epoxy resin used in Example 2 is the following epoxy resin B2.
[0106] Epoxy resin B1 is an epoxy resin obtained by mixing 60% by weight of bisphenol F type epoxy resin and 40% by weight of bisphenol A type epoxy resin. Here, "YDF-8170" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd. was used as the bisphenol F type epoxy resin. "jER1001" manufactured by Mitsubishi Chemical Corporation was used as the bisphenol A type epoxy resin.
[0107] Epoxy resin B2 is an epoxy resin obtained by mixing 80% by weight of bisphenol F type epoxy resin and 20% by weight of bisphenol A type epoxy resin. Here, "YDF-8170" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd. was used as the bisphenol F type epoxy resin. "jER1001" manufactured by Mitsubishi Chemical Corporation was used as the bisphenol A type epoxy resin.
[0108] As the (C) curing agent, the following two types of curing agents, Curing Agent C1 and Curing Agent C2, were used. Hardener C1: Amine-based hardener, 3,3'-diethyl-4,4'-diaminodiphenylmethane ("KAYAHARDA-A (HDAA)" manufactured by Nippon Kayaku Co., Ltd.). Hardener C2: Imidazole-based hardener ("2P4MHZ-PW" manufactured by Shikoku Chemical Industries Co., Ltd.)
[0109] (D) As a dispersant, a polyether carboxylic acid ("HIPLAAD ED 451" manufactured by Kusumoto Chemicals Co., Ltd.) was used.
[0110] The above components (A) to (D) in the weight ratios shown in Table 1 were mixed using a triple roll to prepare a resin composition for forming a low-voltage varistor.
[0111] <Manufacture of varistors according to the embodiment> To manufacture the varistor, a substrate 12 having comb-shaped electrodes 14a and 14b as shown in FIG. 1 was used. A polyimide film with copper foil having a thickness of 8 μm was used as the substrate 12, and the electrodes 14a and 14b were formed by photolithography. Furthermore, a tin thin film of 0.2 μm was formed by plating on the surfaces of the comb-shaped electrodes 14a and 14b. The line width W of the electrode lines constituting the comb-shaped electrodes 14a and 14b was 35 μm, and the space width S between the electrode lines was 35 μm. The length L of the overlapping portion where the electrode lines of the opposing electrodes 14a and 14b overlap was 10 mm.
[0112] Next, as shown in Fig. 2, the resin compositions for forming low-voltage varistors of the above-mentioned Examples 1 and 2 were applied by screen printing so as to cover the overlapping portions of the comb-shaped electrodes 14a and 14b formed on the surface of the substrate 12 in Fig. 1. Thereafter, the substrate 12 to which the resin composition for forming low-voltage varistors was applied was heated at a temperature of 165°C for 2 hours to form a cured body 16 of the resin composition for forming low-voltage varistors, thereby producing a low-voltage varistor. The thickness of the cured body 16 was 15 µm.
[0113] <Comparative Examples 1 and 2> A commercially available low-voltage multilayer ceramic chip varistor (a chip-type multilayer varistor manufactured by Panasonic) was used as the varistor in Comparative Examples 1 and 2. The product name of the varistor in Comparative Example 1 is "EZJS1VB822," and the product name of the varistor in Comparative Example 2 is "EZJS2VB223."
[0114] <Evaluation> For the above-mentioned Examples 1 and 2 and Comparative Examples 1 and 2, various properties were measured as follows, and the performance was evaluated.
[0115] (Measurement of the current-voltage characteristics of a varistor) The current-voltage characteristics of the examples manufactured as described above and the commercially available comparative low-voltage varistors were measured using a Keithley source meter 2611B. Specifically, the current-voltage characteristics of the varistors were measured by applying various voltages to a pair of electrodes (electrodes 14a and 14b) of the varistor and measuring the current value when a predetermined voltage was applied. Figures 3, 4, 5, and 6 show the current-voltage characteristics of Examples 1 and 2 and Comparative Examples 1 and 2.
[0116] (About varistor voltage) From the current-voltage characteristic measurement data in Figures 3 to 6, the varistor voltage (V 0.1mA ) was obtained. Table 2 shows the varistor voltage (V 0.1mA ) is shown.
[0117] (Calculation of nonlinearity coefficient α) Next, the nonlinearity coefficient α was calculated from the current-voltage characteristic data in Figures 3 to 6. Specifically, the current-voltage characteristic data was analyzed using a simulator, and the following equation was calculated by curve fitting: I = K V α The nonlinearity coefficient α value that fits the above equation was calculated. Table 2 shows the calculation results of the nonlinearity coefficient α of the varistors of the examples and comparative examples. When the nonlinearity coefficient α of a varistor is 7 or more, it can be said that the overvoltage protection characteristics are excellent, and therefore the varistor characteristics are good.
[0118] (Capacitance measurement) The capacitance was measured using an Agilent 4288A capacitance meter at an oscillator voltage of 1 Vrms and an oscillator frequency of 1 kHz. Table 2 shows the measurement results of the capacitance of the varistors of the examples and comparative examples.
[0119] (Evaluation Results) As shown in Table 2, the varistor voltages of the varistors of Examples 1 and 2 were 10V or less, which was lower than that of Comparative Examples 1 and 2. Therefore, it was revealed that the varistors of Examples 1 and 2 have excellent characteristics as low-voltage varistors. In addition, the nonlinear coefficient α of the varistors of Examples 1 and 2 was 7 or more, which was higher than that of Comparative Examples 1 and 2. Therefore, it was revealed that the varistors of Examples 1 and 2 have better overvoltage protection characteristics as varistors. In addition, the capacitance of the varistors of Examples 1 and 2 was 200pF or less, which was lower than that of Comparative Examples 1 and 2. Therefore, it was revealed that the varistors of Examples 1 and 2 have high impedance at high frequencies and are more excellent as low-voltage varistors in the high frequency range.
[0120] [Table 1]
[0121] [Table 2]
[0122] <Reference Examples and Reference Comparative Examples> Next, a reference example and a reference comparative example of this embodiment will be described. The present invention is not limited to the reference example and the reference comparative example. In the following description, "porous carbon" means carbon aerogel. The carbon aerogel (porous carbon) described below can be used as a raw material (carbon aerogel) of a resin composition for forming a low-voltage varistor for producing the low-voltage varistor of this embodiment.
[0123] <Production of porous carbon> First, the manufacturing method of the porous carbon used in the reference examples and reference comparative examples will be described. Tables 3 and 4 show the materials and manufacturing conditions used in manufacturing the porous carbon used in the reference examples and reference comparative examples. The porous carbons of reference examples 2 to 4 and reference comparative examples 1 to 4 were manufactured by manufacturing method 1 using furfural and phloroglucinol as materials (raw materials). The porous carbons of reference example 1 and reference comparative example 5 were manufactured by manufacturing method 2 using pyromellitic acid and paraphenyldiamine as main materials (raw materials).
[0124] <Production Method 1: Methods for producing porous carbon in Reference Examples 2 to 4 and Reference Comparative Examples 1 to 4> Table 3 shows the blending amounts of the porous carbon material in Reference Examples 2 to 4, and Table 4 shows the blending amounts of the porous carbon material in Reference Comparative Examples 1 to 4.
[0125] (The process of preparing materials) In the method for producing porous carbon (production method 1) of Reference Examples 2 to 4 and Reference Comparative Examples 1 to 4, first, the predetermined amounts of furfural and phloroglucinol shown in Tables 3 and 4 were prepared.
[0126] (Pretreatment process) Next, phloroglucinol was dissolved in ethanol. Next, furfural was dissolved in the ethanol solution of phloroglucinol. During this dissolution, ethanol was used so that the total weight of phloroglucinol and furfural was the initial concentration shown in Tables 3 and 4. In Production Method 1, the initial concentration (wt%) refers to the concentration of the total amount of phloroglucinol and furfural in the ethanol solution (raw material concentration in the solvent).
[0127] (Gelling process) Next, the ethanol solution of phloroglucinol and furfural obtained as described above was stirred, and then allowed to stand at room temperature to form a gel.
[0128] (Cleaning process) Next, the gelled solid was washed. Ethanol was used for washing. The gelled solid was washed by repeatedly adding ethanol to the gelled solid and then draining the added ethanol. The washing was continued until the color of the drained ethanol disappeared.
[0129] (Supercritical drying process) Next, the gelled solid after washing was taken out and supercritically dried. Specifically, the solid was placed in a sealed container and supercritical liquid CO2 was introduced into the sealed container. This state was then maintained for a certain period of time, after which the supercritical liquid CO2 was discharged. Supercritical drying was performed by repeatedly introducing and discharging supercritical liquid CO2.
[0130] (pyrolysis process) The solid obtained after the supercritical drying as described above was placed in a furnace and pyrolyzed by heating in a nitrogen atmosphere at a heating rate of 1°C / min to 800°C or higher (specifically, the firing temperature shown in Tables 3 and 4) in the case of the reference example. After the temperature increase was completed, the temperature was maintained for 30 minutes. As a result, components other than carbon were removed, and porous carbon was obtained.
[0131] (Crushing process) The heated porous carbon was returned to room temperature and pulverized to obtain the porous carbons of Reference Examples 2 to 4 and Reference Comparative Examples 1 to 4.
[0132] <Production Method 2: Method for producing porous carbon of Reference Example 1 and Reference Comparative Example 5> The blending amount of the porous carbon material in Reference Example 1 is shown in Table 3, and the blending amount of the porous carbon material in Reference Comparative Example 5 is shown in Table 4.
[0133] (The process of preparing materials) In the manufacturing method (manufacturing method 2) of the porous carbon of Reference Example 1 and Reference Comparative Example 5, first, the predetermined amounts of pyromellitic acid and paraphenyldiamine shown in Tables 3 and 4 were prepared.
[0134] (Pretreatment process) Next, a polyamic acid solution was synthesized using pyromellitic acid and paraphenyldiamine as materials. In this synthesis, a solvent (dimethylacetamide and toluene) was used in such a weight that the total weight of the raw materials pyromellitic anhydride and paraphenyldiamine in the polyamic acid solution would be the initial concentration shown in Tables 3 and 4. The solvent used was a mixed solvent of dimethylacetamide and toluene. The polyamic acid solution was synthesized by mixing pyromellitic acid and paraphenyldiamine and heating them. As a result, a polyamic acid solution was synthesized. Next, a predetermined amount of pyridine and acetic anhydride shown in Tables 3 and 4 was added to the polyamic acid solution obtained as described above. As a result, a polyimide solution was obtained.
[0135] (Gelling process) Next, the mixture was stirred, and then allowed to stand at room temperature to obtain a gelled solid.
[0136] (Other processes) Thereafter, the washing step, the supercritical drying step, the pyrolysis step, and the pulverization step were carried out in the same manner as in the production method 1, thereby enabling the production of the porous carbons of Reference Example 1 and Reference Comparative Example 5. The temperature after the temperature increase in the heating step was set to the temperatures shown in Tables 3 and 4.
[0137] The pulverization step was carried out so that the average particle size D50 of the porous carbon of the Reference Example and Reference Comparative Example was 25 nm.
[0138] <Scanning electron microscope (SEM) photo> Scanning electron microscope (SEM) photographs of the surfaces of the porous carbons of Reference Example 1, Reference Example 2, and Reference Comparative Example 2 obtained as described above are shown in Figs. 7 to 12. SEM photographs of Reference Example 1 are shown in Fig. 7 (magnification: 10,000 times) and Fig. 8 (magnification: 100,000 times). SEM photographs of Reference Example 2 are shown in Fig. 9 (magnification: 10,000 times) and Fig. 10 (magnification: 100,000 times). SEM photographs of Reference Comparative Example 2 are shown in Fig. 11 (magnification: 10,000 times) and Fig. 12 (magnification: 100,000 times). In the SEM photographs of Reference Example 1 and Reference Example 2, it can be seen that there are many pores less than 1 μm. In contrast, in the SEM photograph of Reference Comparative Example 2, it can be seen that there are not many pores less than 1 μm, and the surface is relatively smooth.
[0139] <Measurement by Raman spectroscopy> The porous carbons of the Reference Example and Reference Comparative Example obtained as described above were measured by Raman spectroscopy to obtain Raman spectra. Figures 13 to 15 show the Raman spectra of Reference Example 1, Reference Example 2, and Reference Comparative Example 2, respectively. The horizontal axis of Figures 13 to 15 represents the Raman shift (unit: cm -1 ) and the vertical axis represents the signal intensity of the Raman scattered light (arbitrary unit).
[0140] The Raman spectrometer used was a Cora 7100 (manufactured by Anton Paar). The laser light used had a wavelength of 532 nm and an intensity of 50 mW, and the measurement time was 60 seconds. As is clear from FIGS. 13 to 15, the Raman spectrum showed a peak at 1590 cm -1 The G-band peak near 1350 cm -1 It can be seen that the D band peak was observed in the vicinity. If necessary, processing such as subtracting the background from the obtained signal can be performed.
[0141] From the Raman spectrum obtained by measurement using Raman spectroscopy, -1 Integrated intensity of the G-band peak near I G , and 1350 cm -1 The integrated intensity of the D band peak near DThe ratio of the integrated intensities of the G band and the D band (I D / I G The ratio of the integrated intensities of the G band and the D band of the porous carbons of the reference example and the reference comparative example (I D / I G ) are shown in Tables 3 and 4.
[0142] Similarly, the maximum intensity M of the G band peak was measured by Raman spectroscopy. G , and the maximum intensity of the D band peak M D The ratio of the maximum intensities of the G and D band peaks (M D / M G The maximum intensity ratio of the peaks of the G band and the D band in the reference example and the reference comparative example (M D / M G ) are shown in Tables 3 and 4.
[0143] <Materials and blending ratio of resin composition> The materials used in the resin compositions of the Reference Examples and Reference Comparative Examples are as follows: Tables 3 and 4 show the blending ratios of the materials in the Reference Examples and Reference Comparative Examples.
[0144] (Epoxy resin) The epoxy resin used in the reference examples and reference comparative examples was a mixture of bisphenol F type epoxy resin (Nippon Steel Sumitomo Metal Corporation, product number "YDF-8170") (80% by weight) and bisphenol A type epoxy resin (Mitsubishi Chemical Corporation, product number "1001") (20% by weight).
[0145] (hardening agent) In the resin compositions of the reference examples and the reference comparative examples, a mixture of an amine-based curing agent and an imidazole-based curing agent was used as the curing agent.
[0146] As the amine-based hardener, "KAYAHARD AA (HDAA)" (3,3'-diethyl-4,4'-diaminodiphenylmethane) manufactured by Nippon Kayaku Co., Ltd. was used.
[0147] As the imidazole-based curing agent, "2P4MHZ-PW" manufactured by Shikoku Chemical Industries Co., Ltd. was used.
[0148] (Epoxy resin and hardener mixing ratio) The amounts of epoxy resin and hardener (total 100% by weight) were 67.63% by weight of epoxy resin, 25.61% by weight of amine-based hardener, and 6.76% by weight of imidazole-based hardener.
[0149] (Porous carbon (carbon aerogel)) In the resin compositions of the Reference Examples and Reference Comparative Examples, the amounts of epoxy resin and curing agent mixed were 100 parts by weight, and 5 parts by weight of porous carbon was used.
[0150] (Other Ingredients) In the resin compositions of the Reference Examples and Reference Comparative Examples, in addition to the epoxy resin, the curing agent, and the porous carbon, 0.50 parts by weight of a silane coupling agent (KBM-403, manufactured by Shin-Etsu Silicones Co., Ltd.) and 0.25 parts by weight of a dispersant (HIPLAAD ED-451, manufactured by Kusumoto Chemicals Co., Ltd.) were used, with the blending amounts of the epoxy resin and the curing agent being 100 parts by weight.
[0151] Next, the epoxy resin, curing agent, porous carbon, silane coupling agent, and dispersant in the above-mentioned compounding ratio were mixed in a planetary mixer, and further dispersed in a three-roll mill to form a paste, thereby producing a paste for forming a varistor element.
[0152] <Prototype varistor element> 1, a substrate 12 having comb-shaped electrodes 14a and 14b was used. A multilayer printed wiring board (with copper foil) made of FR-4 was used as the substrate 12. The electrodes 14a and 14b were formed by patterning the copper foil of the multilayer printed wiring board.
[0153] Next, as shown in Fig. 2, the resin compositions of the Reference Example and Reference Comparative Example produced as described above were screen-printed to cover the comb-shaped electrodes 14a and 14b formed on the surface of the substrate 12, and the epoxy resin was cured to form a cured body 16. The epoxy resin was cured by maintaining it at a temperature of 165°C for 2 hours. The thickness of the epoxy resin after curing was 90 µm in all cases. In this manner, the varistor elements of the Reference Example and Reference Comparative Example were produced.
[0154] <Measurement of the current-voltage characteristics of a varistor element and calculation of the nonlinearity coefficient α> The current-voltage characteristics of the varistor elements of the reference example and reference comparative example fabricated as described above were measured. Specifically, a predetermined voltage was applied to a pair of electrodes (electrodes 14a and 14b) of the varistor element, and the current value that flowed at that time was measured, thereby measuring the current-voltage characteristics of the varistor element.
[0155] <Calculation of nonlinearity coefficient α> The current-voltage characteristic of a varistor element is I=K V, where K is a constant and α is a nonlinearity coefficient. α The nonlinearity coefficient α was calculated by fitting from the current-voltage characteristics of the varistor element. Tables 3 and 4 show the calculation results of the nonlinearity coefficient α of the varistor elements of the reference example and reference comparative example. When the nonlinearity coefficient α of a varistor element is 6.5 or more, it can be said to have appropriate varistor characteristics that can withstand use.
[0156] As is clear from Tables 3 and 4, the nonlinearity coefficients α of Reference Examples 1 to 4 were all 6.5 or more, which were higher than those of the above-mentioned Comparative Examples 1 and 2. This is because the integrated intensity I G and the integrated intensity of the D band peak I D The ratio (I D / I GThis shows that if a resin composition containing porous carbon with a maximum intensity M G and the maximum intensity of the D band peak M D Ratio (M D / M G ) was above 0.80.
[0157] In contrast, the nonlinearity coefficients α of the porous carbons of Reference Comparative Examples 1 to 5 were all 2.2 or less, and did not have suitable varistor characteristics for use. G and the integrated intensity of the D band peak I D The ratio (I D / I G ) was less than 2. In addition, the maximum intensity M G and the maximum intensity of the D band peak M D Ratio (M D / M G ) was less than 0.8.
[0158] From the above, it is clear that by using a resin composition containing porous carbon having a predetermined Raman spectrum, a varistor element having suitable varistor characteristics that can withstand use can be obtained.
[0159] [Table 3]
[0160] [Table 4] [Explanation of symbols]
[0161] 10. Barista 12 Base material 14a, 14b electrode 16 Hardened body
Claims
1. A low-voltage varistor comprising a cured product of a low-voltage varistor-forming resin composition, The resin composition for forming a low-voltage varistor comprises (A) carbon nanotubes, or carbon nanotubes and carbon aerogel; (B) at least one selected from an epoxy resin and an acrylic resin; Including, A low-voltage varistor, characterized in that the content of carbon nanotubes is 0.01 part by weight or more and less than 0.05 part by weight per 100 parts by weight of the epoxy resin (B).
2. A low-voltage varistor comprising a cured product of a resin composition for forming a low-voltage varistor, The resin composition for forming a low-voltage varistor comprises (A) a carbon aerogel; (B) at least one selected from an epoxy resin and an acrylic resin; A low voltage varistor comprising:
3. 2. The low-voltage varistor according to claim 1, wherein the varistor voltage is 0.3 to 10 V when the inflow current of the low-voltage varistor is 0.1 mA.
4. The current-voltage characteristics of a low-voltage varistor are as follows: I = K. α 4. A low-voltage varistor according to claim 1 or 3, characterized in that, when expressed as (where V is the applied voltage, I is the inflow current, K is a constant, and α is a nonlinearity coefficient), the nonlinearity coefficient α is 7 to 20.
5. 5. A low-voltage varistor according to claim 1, characterized in that the capacitance is 0.5 to 200 pF.
6. A circuit board mounting the low-voltage varistor according to any one of claims 1 to 5.
7. A semiconductor component package incorporating the low-voltage varistor according to any one of claims 1 to 5.
8. An interposer equipped with the low-voltage varistor according to any one of claims 1 to 5.
Citation Information
Patent Citations
PTC composition
JP1990145659A
Electric resistance element
JP1994215903A
Laminated ceramic varistor and method for manufacture thereof
JP2001093706A
Resin composition, paste for forming a varistor element, and varistor element
US10141090B2
Resin composition, paste for forming a varistor element, and varistor element
US20180197663A1